GC-B Deficient Mice With Axon Bifurcation Loss Exhibit Compromised Auditory Processing - Wolter, Steffen; Möhrle, Dorit; Schmidt, Hannes; Pfeiffer, Sylvia; Zelle, Dennis; Eckert, Philipp; Krämer, Michael; Feil, Robert; Pilz, Peter K. D.; Knipper, Marlies; Rüttiger, Lukas (Frontiers in Neural Circuits, 2018)
Sensory axon T-like branching (bifurcation) in neurons from dorsal root ganglia (DRG) and cranial sensory ganglia (CSG) depends on the molecular signaling cascade involving the secreted factor C-type natriuretic peptide (CNP), the natriuretic peptide receptor guanylyl cyclase B (GC-B; also known as Npr2) and cGMP-dependent protein kinase I (cGKI, also known as PKGI). The bifurcation of cranial nerves is suggested to be important for information processing by second-order neurons in the hindbrain or spinal cord. Indeed, mice with a spontaneous GC-B loss of function mutation (Npr2cn/cn) display an impaired bifurcation of auditory nerve (AN) fibers. However, these mice did not show any obvious sign of impaired basal hearing. Here, we demonstrate that mice with a targeted inactivation of the GC-B gene (Npr2lacZ/lacZ, GC-B KO mice) show an elevation of audiometric thresholds. In the inner ear, the cochlear hair cells in GC-B KO mice were nevertheless similar to those from wildtype mice, justified by the typical expression of functionally relevant marker proteins. However, efferent cholinergic feedback to inner and outer hair cells was reduced in GC-B KO mice, linked to very likely reduced rapid efferent feedback. Sound-evoked AN responses of GC-B KO mice were elevated, a feature that is known to occur when the efferent axo-dendritic feedback on AN is compromised. Furthermore, late sound-evoked brainstem responses were significantly delayed in GC-B KO mice. This delay in sound response was accompanied by a weaker sensitivity of the auditory steady state response (ASSR) to amplitude-modulated sound stimuli. Finally, the acoustic startle response (ASR) – one of the fastest auditory responses – and the prepulse inhibition (PPI) of the ASR indicated significant changes in temporal precision of auditory processing. These findings suggest that GC-B-controlled axon bifurcation of spiral ganglion neurons is important for proper activation of second-order neurons in the hindbrain and is a prerequisite for proper temporal auditory processing likely by establishing accurate efferent top-down control circuits. These data hypothesize that the bifurcation pattern of cranial nerves is important to shape spatial and temporal information processing for sensory feedback control.